2001
DOI: 10.1177/000348940111000212
|View full text |Cite
|
Sign up to set email alerts
|

Thyroarytenoid Muscle: Functional Subunits Based on Morphology and Muscle Fiber Typing in Cats

Abstract: Using parvalbumin immunohistochemistry to determine the distribution of muscle fiber types in the feline thyroarytenoid muscle (TA), we clearly distinguished the vocalis (with predominance of "slow" type 1 fibers) from the external TA (in which "fast" type 2 fibers predominated, especially in its rostral part). Reconstruction of serial frontal sections of the TA allowed the stereoscopic study of each division. The existence of a rudimentary laryngeal ventricle separating the true and false vocal folds in cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…This bundle is constituted mainly of type II muscle fibers, which allow fast contraction and little resistance to fatigue. [28][29][30] These findings suggest that 7-minute duration of tongue trill performance is excessive and tends to harm the voice instead of bringing positive effects. The vocal worsening at this moment may be regarded as vocal fatigue, because it causes negative adaptation after the voice's lengthy use in such a situation.…”
Section: Discussionmentioning
confidence: 99%
“…This bundle is constituted mainly of type II muscle fibers, which allow fast contraction and little resistance to fatigue. [28][29][30] These findings suggest that 7-minute duration of tongue trill performance is excessive and tends to harm the voice instead of bringing positive effects. The vocal worsening at this moment may be regarded as vocal fatigue, because it causes negative adaptation after the voice's lengthy use in such a situation.…”
Section: Discussionmentioning
confidence: 99%
“…Their results and those of several other studies have revealed differences in MHC isoform expression and/or muscle fiber types between the medial division, commonly referred to as the vocalis region, and the lateral (also referred to as external in some reports) division of the canine (37), feline (16), and human thyroarytenoid muscle (13,19,36). Furthermore, Yokoyama et al (38) and Imamura et al (16) reported that heterogeneity in muscle fiber-type distribution exists within the lateral (external) division of feline thyroarytenoid muscle. It is therefore reasonable to expect that even more extensive regional differences in MHC isoform expression exist between specific compartments in canine thyroarytenoid muscle in addition to those between the vocalis and lateral divisions reported previously (37).…”
mentioning
confidence: 82%
“…10 The authors' results are confirmed by other studies in cats, in which the authors reported that the anatomic individualization of the divisions of the TA muscle may suggest that they play distinct physiological roles and may imply that they should not be considered as a single functional unit. 23 Similarly, other authors have reported that for the TA muscle, fiber attachment to the thyroid cartilage is curved, so that fiber length is not uniform (nearly a 12% variation). Thus, when the insertion and origin surfaces of a muscle are not parallel to each other, the fibers on one side of the sample are different in length from those on the other side.…”
Section: E24mentioning
confidence: 88%
“…Moreover, the TA muscle is the only muscle that selectively controls different parts of the vocal fold. Thus, the selective control of different regions of the vocal fold can be explained, at least in part, by fact that the organization of muscle fibers in the TA 10,23,24 is similar to that seen in the TO muscles. Furthermore, their results can be considered as general reference points for future studies aimed at further elucidating the relationship between peripheral nerve regeneration and any possible relation to the pathogenesis of diseases, such as idiopathic laryngeal hemiparalysis and hemiatrophy of the TO muscles.…”
Section: E25mentioning
confidence: 99%